2000
DOI: 10.1097/00004647-200001000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia on Hippocampal Slices from Mice Deficient in Dystrophin (mdx) and Isoforms (mdx3cv)

Abstract: Slices from control C57, mdx, and mdx3cv mice were made hypoxic until both field excitatory postsynaptic potential (fEPSP) and presynaptic afferent volley (AV) disappeared (H1). After reoxygenation and recovery of fEPSP, a second and longer hypoxic test (H2) lasted 3 minutes beyond the time required to block AV. When slices were kept in 10 mmol/L glucose, HI abolished AV 37 and 19% earlier in slices from mdr and mdx3cv mutants than in control slices (where HI = 12 +/- 4.6 minutes, mean +/- SD). During H2 or wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Localization of Utrn isoforms in vascular endothelium, the choroid plexus and SCO suggests the potential role of Utrn‐A and ‐B in CSF formation and maintaining the BBB. Coupled with previous studies on Utrn expression and our demonstration of Utrn‐A expression in hippocampal neurons (14), it supports a structural and/or protective role for Utrn. The resources generated here, including the Utrn‐A‐ and Utrn‐B‐specific q‐PCR TaqMan assay, promoter constructs and antibodies, will provide useful reagents to be employed in subsequent investigations to test these hypotheses and further understand regulatory mechanism(s) of Utrn‐A and ‐B in normal and dystrophin‐deficient tissues including CNS, as well and facilitate developing Utrn upregulation strategies for DMD.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Localization of Utrn isoforms in vascular endothelium, the choroid plexus and SCO suggests the potential role of Utrn‐A and ‐B in CSF formation and maintaining the BBB. Coupled with previous studies on Utrn expression and our demonstration of Utrn‐A expression in hippocampal neurons (14), it supports a structural and/or protective role for Utrn. The resources generated here, including the Utrn‐A‐ and Utrn‐B‐specific q‐PCR TaqMan assay, promoter constructs and antibodies, will provide useful reagents to be employed in subsequent investigations to test these hypotheses and further understand regulatory mechanism(s) of Utrn‐A and ‐B in normal and dystrophin‐deficient tissues including CNS, as well and facilitate developing Utrn upregulation strategies for DMD.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, brain areas of mdx mice where Utrn‐A was found upregulated are the major areas of dystrophin expression (28, 32). Previous studies have shown that the cerebral cortex and brainstem regions of mdx has 50% decrease in neuronal number and neural shrinkage (44), and hippocampal neurons in mdx mice are known to be more susceptible to hypoxia‐induced damage (14). Therefore, Utrn upregulation observed in mdx CNS suggests a potential neuroprotective effect from neuropathological insults.…”
Section: Discussionmentioning
confidence: 99%
“…This was further investigated by exposing mdx hippocampal tissue slices, kept at different concentrations of glucose, to an irreversible hypoxic failure; mdx slices kept at 10 mM glucose demonstrated more susceptibility to hypoxia when compared with controls, whereas those kept at 4 mM glucose demonstrated less susceptibility compared with controls (Godfraind et al, 2000). These findings reflect a decreased bioenergetics buffering capacity (Anderson et al, 2002).…”
Section: Alterations Due To Lack Of Dystrophinmentioning
confidence: 99%
“…Yoshihara et al (2003) suggested that the increased sensitivity to hypoxia found by Mehler et al (1992) may be due to impaired function of inhibitory synapses at this site. Another group (Godfraind et al 1998(Godfraind et al , 2000 has shown increased susceptibility of mdx hippocampal tissue slices to irreversible hypoxic failure when kept in 10 mM glucose, but less susceptibility of mdx slices when kept in 4 mM glucose, in agreement with Wallis et al (2004). The latter group suggest that the decrease in GLUT1 and GLUT3 expression they found is most likely related to decreased synaptic integrity, resulting in decreased activity and decreased glucose utilization.…”
Section: Biochemistrymentioning
confidence: 78%